Nostalgic Sentiment And Cultural And Creative Industries In Regional Development: A Slovak Case Study - Borseková, Kamila; Cole, David; Petríková, Katarína; Vaňová, Anna (Quaestiones Geographicae, 2015)
In Slovakia, there are three unique, historical mining towns, Banská Bystrica, Banská Štiavnica and Kremnica, that have been successfully turned into creative cultural centres. The historical and cultural values of those towns have stood the test of time and become a magnet for a new and creative class of people looking to escape the brutality of high modernity (modern urban centres) and find a source of inspiration based on historical nostalgic sentimentalism — the basis for a new creative and cultural industry for rural areas. The main objective of this paper is to analyse the cultural and creative industries of these three unique historical mining centres with an eye to replicating their knowledge in other communities in economic stress. The paper will first explore concepts relating to cultural and creative industries with an eye towards nostalgic sentimentalism that is an important antithesis to high modernity, and even post-modernity. The second part will analyse the cultural and creative industries of the three centres based on primary data collected from several research projects in this area. The final part will provide some recommendations for the facilitation of creative and cultural enterprises in regional redevelopment. It also contains policy recommendations for the self-government of the region for a more effective and rational exploitation of the existing potential hiding in plain view.